The Use of Alternative Energy as a Driver Fishing Boat - IS, Nina Paramytha; Ariyadi, Tamsir (Universitas Ahmad Dahlan, 2023)
The use of outboard engines commonly used by fishing boats is considered no longer effective, considering the price of BBM (Fuel Oil) which always increases and the effects caused by the use of outboard engines are not environmentally friendly such as producing noise and air pollution caused. This research aims to overcome the problems of using outboard engines by utilizing solar panels to convert sunlight into electrical energy and DC 775 motors as boat propulsion. The use of solar panels with a tracker system to maximize solar panels in producing electrical energy which is then stored in a battery to drive a DC motor. The results of the calculation of a battery with a capacity of 20 Ah can drive the boat for 3.7 hours, where fishermen need 1 liter of fuel to run the outboard engine for 30 minutes. The maximum boat speed generated is 5.76 knots. The results of the analysis in terms of costs incurred for fuel operations are 0% because they utilize sunlight and there is no pollution and noise generated when the boat works. Future development can replace the battery with a larger capacity and add solar panels for faster battery charging. With this research, researchers hope to help fishermen in reducing operational costs and the success of catching more fish.